Dehydrogenative TEMPO‐Mediated Formation of Unstable Nitrones: Easy Access to N‐Carbamoyl Isoxazolines. Issue 34 (17th July 2015) - Gini, Andrea; Segler, Marwin; Kellner, Dominik; Mancheño, Olga García
Abstract N‐carbamoyl nitrones represent an important class of reagents for the synthesis of a variety of natural and biologically active compounds. These compounds are generally converted into valuable 4‐isoxazolines upon cyclization reaction with dipolarophiles. However, these types of N‐protected nitrones are highly unstable, which limits their synthesis, storage and practical use, enforcing alternative lengthy or elaborated synthetic routes. In this work, a 2, 2, 6, 6‐tetramethylpiperidin‐1‐oxyl (TEMPO)‐mediated formal "dehydrogenation" of N‐protected benzyl‐, allyl‐ and alkyl‐substituted hydroxylamines followed by in situ trapping of the generated unstable nitrones into N‐carbamoyl 4‐isoxazolines is presented. A plausible mechanism is also proposed, in which the dipolarophile shows an important assistant role in the generation of the active nitrone intermediate. This simple protocol avoids the problematic isolation of N‐carbamoyl protected nitrones, providing new synthetic possibilities in isoxazoline chemistry.